High power YAG/Nd:YAG/YAG ceramic planar waveguide laser. (13th February 2017) - Rao, Han; Liu, Zhaojun; Cong, Zhenhua; Huang, Qingjie; Liu, Yang; Zhang, Sasa; Zhang, Xingyu; Feng, Chao; Wang, Qingpu; Ge, Lin; Li, Jiang
Abstract: A high power YAG/Nd:YAG/YAG ceramic planar waveguide laser was demonstrated. For continuous wave regime, a maximum output power of 10.4 W at a center wavelength of 1064.6 nm was obtained under an absorbed pump power of 17.4 W, corresponding to an optical-to-optical conversion efficiency of 59.8%. For acousto-optically Q -switched operation, we obtained 2.5 W of output power at a pulse repetition frequency of 10 kHz. The pulse duration was 6.5 ns with peak power and pulse energy of 38.5 kW and 0.25 mJ, respectively.